Offshoring, Exporting, and Jobs - Jose L. Groizard; Priya Ranjan; Antonio Rodriguez-Lopez (Center for Economic Studies and ifo Institute (CESifo), 2013)
We construct a two-sector model - one producing a homogeneous good and the other producing differentiated goods - with labor market frictions to study the impact of offshoring on intrafirm, intrasectoral, and intersectoral reallocation of jobs, and on the economy-wide unemployment rate. A reduction in the offshoring cost affects intrafirm and intrasectoral reallocation in the differentiated-good sector through a job-relocation effect, a productivity effect, and a competition effect. The key parameters determining the impact of offshoring on reallocation of jobs at various margins as well as on the economy-wide unemployment rate are the elasticity of substitution between inputs and the elasticity of demand for differentiated goods. Allowing differentiated-good firms to export creates an additional channel through which a reduction in the cost of offshoring affects jobs and unemployment. We also show that the implications of a reduction in the cost of trading final goods are different from those of a reduction in the offshoring cost.
Keywords: F12; F16; 330; heterogeneous firms; offshoring costs; search frictions; unemployment